Innovations in rural and agricultural finance: Combining extension services with agricultural credit: The experience of BASIX India - Mahajan, Vijay; Vasumathi, K. (International Food Policy Research Institute, 2010)
India has nearly 90 million farm households. More than 80 percent of these farmers operate on a small or marginal scale, farming less than two hectares of land. They also usually have one or two buffaloes or cows, reared for milk and dung. Most of these small and marginal farmers fall below the poverty line. To reduce overall poverty in India, it is important to enhance the incomes of small and marginal farmers. One way to do that is to provide credit so they can get access to yield-enhancing inputs like seed, fertilizer, and cattle feed, as well as acquire irrigation pumps and crossbred cattle. But these kinds of investments alone will not raise farmers' incomes. Agricultural and livestock development services are also crucial to give farmers knowledge of improved practices and strengthen their links to markets.